Diagnostic Value of Abdominal Ultrasonography in Patients with Blunt Abdominal Trauma - Nnamonu, Michael I (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Various investigative modalities are used to detect intra-abdominal injury requiring surgical intervention. Ultrasonography (US) is a cheap, readily available, safe and non-invasive investigation used in the evaluation of patients with blunt abdominal trauma. Patients are subjected to no added risk of radiation. AIMS: The aim of this study was to evaluate the diagnostic value of US in patients with blunt abdominal trauma. MATERIALS AND METHODS: Patients who had US for blunt abdominal trauma were prospectively evaluated from 1 January 2006 to 31 December 2007. A total of 57 patients were included is this study. US results in each patient were classified as true positive (TP), false positive (FP), false negative (FN) or true negative (TN) by comparing with findings at either diagnostic peritoneal lavage or surgery. Sensitivity, specificity, positive and negative predictive values (NPV) and diagnostic accuracy of US in detecting free fluid and in detecting the visceral parenchymal injury were calculated using two by two tables. The Epi Info statistical software version 3.4.1 was used for data analysis. RESULTS: By scanning to detect free fluid, TPs were 46, FPs three, FNs two and TNs six. Sensitivity, specificity, positive and NPV and the diagnostic accuracy were 96%, 67%, 94%, 75% and 91% respectively. By scanning to detect the parenchymal injury, TPs were 24, FPs 15, FNs 10 and TNs 8. Sensitivity, specificity, positive and NPV and diagnostic accuracy were 71%, 35%, 62%, 44% and 56% respectively. CONCLUSION: US has a high diagnostic value in the screening of patients with blunt abdominal trauma. Scanning for the presence of free fluid yields better results than scanning for the visceral parenchymal injury.